Interactions between triterpenes and a P-I type snake venom metalloproteinase: Molecular simulations and experiments (2018)
ABSTRACT: Small molecule inhibitors of snake venom metalloproteinases (SVMPs) could provide a means to rapidly halt the progression of local tissue damage following viperid snake envenomations. In this study, we examine the ability of candidate compounds based on a pentacyclic triterpene skeleton to inhibit SVMPs. We leverage molecular dynamics simulations to estimate the free energies of the candidate compounds for binding to BaP1, a P-I type SVMP, and compare these results with experimental assays of proteolytic activity inhibition in a homologous enzyme (Batx-I). Both simulation and experiment suggest that betulinic acid is the most active candidate, with the simulations predicting a standard binding free energy of DG = 11.0 1.4 kcal/mol. The simulations also reveal the atomic interactions that underlie binding between the triterpenic acids and BaP1, most notably the electrostatic interaction between carboxylate groups of the compounds and the zinc cofactor of BaP1. Together, our simulations and experiments suggest that occlusion of the S10 subsite is essential for inhibition of proteolytic activity. While all active compounds make hydrophobic contacts in the S10 site, b-boswellic acid, with its distinct carboxylate position, does not occlude the S10 site in simulation and exhibits negligible activity in experiment.